Spacing and sowing density on upland cotton in South-West of Bahia State - Beltrão, Napoleão E. de Macêdo; Azevedo, Demóstenes M. P. de; Vieira, Dirceu J.; Nóbrega, Laudemiro B. da (Pesquisa Agropecuaria Brasileira, 2014)
Four field experiments were carried out in Yuyu Valley, South-West of Bahia State, Brazil, during the years 1980/81, 81/82, and 82/83 in medium and high natural fertility soils to define the best spacing (between rows) and sowing density on upland cotton for that region. The experimental design used was a factorial with common and non common treatments. The spacings tested were: 1.00 m; 0.80 m; and 0.60 m between rows. These spacings were common to all places and years, while 1,20 m was common to only three places. The sowing densities tested were 3; 7; 11; and 15 plants per meter of row and no thinning. Each experiment was analised separately and fourteen dependent variables were analised in a combined analysis of variance. The results showed to be 0.60 m the most productive spacing as compared with 1.00 m getting yield increment of 13.9%. In terms of sowing density, no significant differences in cotton yield were obtained among treatments.